Physical Activity and Attitudes Toward Social Media Use of Active Individuals During the COVID-19 Pandemic in Saudi Arabia: Cross-Sectional Survey - AlMarzooqi, Mezna A. (Frontiers in Psychology, 2021)
Background: Social media became an integral part of the lives of people because it encourages social relations and shares interests, activities, and real-life connections. As quarantine and lockdown orders are prolonged, many people, as well as those physically active individuals, typically responded to this stressful condition by using social media platforms. Objective: This study aimed to examine the level of physical activity of physically active individuals and their attitudes toward social media use during the COVID-19 pandemic. Methods: A descriptive cross-sectional survey was conducted among physically active individuals in Saudi Arabia between June 2020 and July 2020. An online survey was employed among eligible participants who completed a self-administered questionnaire that covered reasons for physical activity and attitudes toward social media platforms during the COVID-19 pandemic. Results: Of these 323 participants, 29.1% were in the age group of 18–24 years, 66.6% were women, and 67.8% were single. The proportion of participants whose metabolic equivalent of tasks-min/week from vigorous activity <1,680 was 31.9%, and all of the participants follow people or pages in social media related to sports teams and fitness models. The average number of hours spent on social media per day was 2.95 ± 0.90 h. The majority of the participants showed positive attitudes toward social media used for exercise and physical activity. Of the eight variables, age, level of physical activity, and the average of hours spent on social media emerged as significant predictors of attitudes toward the use of social media (P < 0.05). Conclusions: The present survey results indicate adverse consequences of home quarantine as reflected by a small proportion of participants who had differences in levels of vigorous activities during the COVID-19 pandemic in Saudi Arabia. Social media appears to be a key avenue to promote and disseminate health interventions to promote physical activity during this COVID-19 pandemic.